Childhood symptoms of attention‐deficit/hyperactivity disorder and borderline personality disorder. (23rd July 2022) - Tiger, Annika; Ohlis, Anna; Bjureberg, Johan; Lundström, Sebastian; Lichtenstein, Paul; Larsson, Henrik; Hellner, Clara; Kuja‐Halkola, Ralf; Jayaram‐Lindström, Nitya
Abstract: Objective: Childhood attention‐deficit /hyperactivity disorder (ADHD) is known to be associated with adult Borderline Personality Disorder (BPD). We investigated if any of the subdimensions of childhood ADHD, that is, impulsivity, inattention, or hyperactivity was more prominent in this association. Methods: In a nation‐wide cohort ( N  = 13, 330), we utilized parent reported symptoms of childhood ADHD and clinically ascertained adult BPD diagnoses. The summed total scores of ADHD symptoms and its three subdimensions were used and standardized for effect size comparison. Associations were analyzed using Cox regression with sex and birth‐year adjustments. Secondary outcomes were BPD‐associated traits (i.e., self‐harm and substance use) analyzed using logistic‐ and linear regression respectively. Results: ADHD symptom severity was positively associated with BPD with a hazard ratio (HR) of 1.47 (95% confidence interval [CI]: 1.22–1.79) per standard deviation increase in total ADHD symptoms. Impulsivity was the most prominent subdimension with the only statistically significant association when analyzed in a model mutually adjusted for all ADHD subdimensions—HR for inattention: 1.15 (95% CI: 0.85–1.55), hyperactivity: 0.94 (95% CI: 0.69–1.26), impulsivity: 1.46 (95% CI: 1.12–1.91). In secondary analyses, weak positive associations were seen between total ADHD symptom score and self‐harm and substance use. In analyses by subdimensions of ADHD, associations were weak and most prominent for inattention in the model with self‐harm. Conclusion: Childhood ADHD symptoms were associated with subsequent development of BPD diagnosis and appeared to be driven primarily by impulsivity. Our findings are important for understanding the association between childhood symptoms of ADHD and subsequent BPD.